Kedudukan ÅšrÄ« Ká¹›á¹£á¹‡a pada DevÄ« BhÄgavata PurÄá¹‡a Perspektif acintya-bhedÄbheda-tattva - Mahaputra, I Gusti Ngurah Agung Mahesa (Institut Hindu Dharma Negeri Denpasar, 2018)
DeviÌ„ BhÄgavata and ÅšriÌ„mad-BhÄgavatam from the theological aspects both affirm Lord Ká¹›á¹£á¹‡a as Puruá¹£a (ancient God). It is something unique that DeviÌ„ BhÄgavata in the whole of Skanda always position Ä€dyÄsÌakti as Almighty God (supreme Brahman and also mÄyÄ), but at the same time in Skanda 9, DeviÌ„ BhÄgavata also confirmed Lord Ká¹›á¹£á¹‡a as Puruá¹£a. In general we know that DurgÄ or Åšakti refers to potential or energy while Åšiva or Ká¹›á¹£á¹‡a is the source of potential or possessing energy, but in the proposition of DeviÌ„ BhÄgavata, the Ä€dyÄsÌakti acts as Brahman or Puruá¹£a and at the same time MahÄmÄyÄ. In another narration on DeviÌ„ BhÄgavatam also states that Ä€dyÄsÌakti as primal sÌakti (Nirguá¹‡a Brahman) and positions Puruá¹£a as His instrument.